Parents’ Perception of School Violence, Awareness of Risk Factors, and School Safety: An Ecological Perspective - Hussein Hassan Soliman; Jennifer Koran; Abdel-Salam Gomaa (International Journal of School Social Work, 2018)
Parents’ concerns about school violence and school safety have been documented in many research studies (Diaz-Vicario & Sallan, 2017; Hundeloh & Hess, 2003). Understanding parents’ perceptions of school safety can be an important issue that will guide teachers (Bosworth, Ford, & Hernandaz, 2011), administrators and staff (Heisterkamp, & Fleming, 2011), and legislators (Elliott, 2015) in setting strategies to enhance school safety and school climate. The purpose of this study is to identify factors that contribute to parents’ views of school safety. Based on existing literature, this study developed a model of one main endogenous variable – feelings of instructional safety – and seven additional exogenous and endogenous variables – awareness of bulling behavior, awareness of school violence, parent visits school, communicating perspective, experience with violence, knowledge of risk, resources and school measures. A total of 403 parents who reside in the southern part of Illinois participated in the survey. Path analysis with exploratory modifications was used to examine the study model and the study hypotheses. The study findings suggested parents’ visits to school and parents’ experience with violence had statistically significant direct effects on their awareness of school violence, which had a significant direct effect on parents’ feelings of instructional safety. Although exploratory, this study provided important insights on school violence, school safety and school climate, and implications for future research in this area are discussed.
Keywords: parent - school safety - ecological perspective - risk